2017
DOI: 10.1371/journal.pone.0170314
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Mutant SEMA3A Protein with Diminished Signalling Capacity Does Not Alter ALS-Related Motor Decline, or Confer Changes in NMJ Plasticity after BotoxA-Induced Paralysis of Male Gastrocnemic Muscle

Abstract: Terminal Schwann cells (TSCs) are specialized cells that envelop the motor nerve terminal, and play a role in the maintenance and regeneration of neuromuscular junctions (NMJs). The chemorepulsive protein semaphorin 3A (SEMA3A) is selectively up-regulated in TSCs on fast-fatigable muscle fibers following experimental denervation of the muscle (BotoxA-induced paralysis or crush injury to the sciatic nerve) or in the motor neuron disease amyotrophic lateral sclerosis (ALS). Re-expression of SEMA3A in this subset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…Our results show that female fast-fatigable MUs (surface of the tibialis anterior; see Materials and Methods) are much more likely to form expansions in SOD1 G37R / YFP mice, resulting in a net increase in MU size in females but not in males. This result is consistent with previous findings on botulinum toxin-induced axonal sprouting (Moloney et al, 2017), where fast-fatigable motor axons were more likely to sprout in female mice. Interestingly, this increased dynamism is associated with an earlier onset of motor deficits and an exacerbated pathology in our female mice, as shown by the loss of grip strength and the neuromuscular and spinal cord histopathology.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results show that female fast-fatigable MUs (surface of the tibialis anterior; see Materials and Methods) are much more likely to form expansions in SOD1 G37R / YFP mice, resulting in a net increase in MU size in females but not in males. This result is consistent with previous findings on botulinum toxin-induced axonal sprouting (Moloney et al, 2017), where fast-fatigable motor axons were more likely to sprout in female mice. Interestingly, this increased dynamism is associated with an earlier onset of motor deficits and an exacerbated pathology in our female mice, as shown by the loss of grip strength and the neuromuscular and spinal cord histopathology.…”
Section: Discussionsupporting
confidence: 93%
“…This scenario could also explain why females tended to have higher global levels of NMJ denervation despite the similar amount of asynchronous NMJ losses between males and females. However, this scenario is not entirely consistent with the notion that female fast-fatigable motor axons are intrinsically more inclined to sprout (Moloney et al, 2017). Hence, additional studies aimed at manipulating MUs expansions levels in males and females are required to determine whether they represent an adaptive or a maladaptive response in female SOD1 G37R mice.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The involvement of Sema3A in the pathogenesis of ALS has been suggested in a number of studies using ALS models in mice with some conflicting results 10 , 19 . Since many core biological processes and genetic elements are conserved between human and mouse, these findings in mice are considered suggestive.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, injecting specific antibodies against NRP1 or manipulating Sema3A expression using miR126-5p resulted in improvement in disease progression in vivo and in vitro (Venkova et al ., 2014; Maimon et al ., 2018). In contrast to these results, a recent study demonstrated that crossing mice expressing a truncated form of Sema3A with SOD1 G93A mice does not result in any rescue effect (Moloney et al ., 2017). An explanation for this contradiction could be the possibility that secreted factors such as Sema3A play a more complex role in the biology of MNs (Zahavi, Maimon and Perlson, 2017).…”
Section: Discussionmentioning
confidence: 75%